2016
DOI: 10.1038/srep37139
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic characterization of neuromelanin granules isolated from human substantia nigra by laser-microdissection

Abstract: Neuromelanin is a complex polymer pigment found primarily in the dopaminergic neurons of human substantia nigra. Neuromelanin pigment is stored in granules including a protein matrix and lipid droplets. Neuromelanin granules are yet only partially characterised regarding their structure and function. To clarify the exact function of neuromelanin granules in humans, their enrichment and in-depth characterization from human substantia nigra is necessary. Previously published global proteome studies of neuromelan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
63
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(72 citation statements)
references
References 34 publications
8
63
1
Order By: Relevance
“…properties to the melanin found in skin, hair and eyes, being insoluble to organic solvents and labelled by silver stains (58,59), which was why it was called "neuromelanin". However, little is known about the biology and the physiological functions of NM.…”
Section: Discussionmentioning
confidence: 99%
“…properties to the melanin found in skin, hair and eyes, being insoluble to organic solvents and labelled by silver stains (58,59), which was why it was called "neuromelanin". However, little is known about the biology and the physiological functions of NM.…”
Section: Discussionmentioning
confidence: 99%
“…44,45 Similarly, mass spectrometry techniques failed to detect significant amounts of typical enzymes and proteins involved in melanogenesis, including tyrosinase, in isolated neuromelanin-containing organelles from human SN. 15,46,47 In contrast, tyrosinase enzymatic activity has been reported in brain extracts from human SN, 41 although at 100,000 times lower than in melanocytes. 48 These inconsistent results could be potentially attributed to the very low levels at which tyrosinase might be actually expressed, if at all, in the brain and further experiments are thus warranted to unambiguously demonstrate or refute the existence of tyrosinase in the human brain.…”
Section: Synthesis Of Neuromelanin: Mechanisms and Significancementioning
confidence: 92%
“…Consistent with the very low levels at which tyrosinase mRNA might be expressed, if at all, in the brain, the actual protein has not been detected in the human brain when using immunohistochemistry or Western blot . Similarly, mass spectrometry techniques failed to detect significant amounts of typical enzymes and proteins involved in melanogenesis, including tyrosinase, in isolated neuromelanin‐containing organelles from human SN . In contrast, tyrosinase enzymatic activity has been reported in brain extracts from human SN, although at 100,000 times lower than in melanocytes .…”
Section: Synthesis Of Neuromelanin: Mechanisms and Significancementioning
confidence: 99%
“…Because neuromelanin granules have been found in lysosomes (13), the accumulation of neuromelanin-like aggregates in mutant dopaminergic neurons suggested that lysosomal function might be impaired. While there was no detectable impairment in lysosomal proteolysis in homozygous DJ-1 mutant neurons at d70 (Fig.…”
Section: Dopamine-mediated Modification Of Glucocerebrosidase (Gcase)mentioning
confidence: 99%